Bacterial Blight of Ficus elastica Caused by Xanthomonas - E. Vanessa Campoverde; Aaron J. Palmateer (EDIS)
In the summer of 2010, leaf blight cases were reported on several Ficus elastica cultivars in Homestead nurseries. Symptoms somewhat resembled those caused by Xanthomonas campestris p.v. fici, but this pathogen has never been reported to occur on Ficus elastica. The outbreak was severe, and the majority of commercial producers in the southern portion of the state were affected. The widespread outbreak from 2010 to date has caused many nurseries to lose entire Ficus elastica crops. This 3-page fact sheet describes the symptoms and disease management recommendations. Written by E. V. Campoverde and A. J. Palmateer, and published by the UF Department of Plant Pathology, April 2013.